Myosin V facilitates polarised E-cadherin secretion - Tanasić, Dajana; Berns, Nicola; Riechmann, Veit (Traffic, 2022)
E-cadherin has a fundamental role in epithelial tissues by providing cell-cell adhesion. Polarised E-cadherin exocytosis to the lateral plasma membrane is central for cell polarity and epithelial homeostasis. Loss of E-cadherin secretion compromises tissue integrity and is a prerequisite for metastasis. Despite this pivotal role of E-cadherin secretion, the transport mechanism is still unknown. Here we identify Myosin V as the motor for E-cadherin secretion. Our data reveal that Myosin V and F-actin are required for the formation of a continuous apicolateral E-cadherin belt, the zonula adherens. We show by live imaging how Myosin V transports E-cadherin vesicles to the plasma membrane, and distinguish two distinct transport tracks: an apical actin network leading to the zonula adherens and parallel actin bundles leading to the basal-most region of the lateral membrane. E-cadherin secretion starts in endosomes, where Rab11 and Sec15 recruit Myosin V for transport to the zonula adherens. We also shed light on the endosomal sorting of E-cadherin by showing how Rab7 and Snx16 cooperate in moving E-cadherin into the Rab11 compartment. Thus, our data help to understand how polarised E-cadherin secretion maintains epithelial architecture and prevents metastasis.